TALABALAR JISMONIY TAYYORGARLIGINI OSHIRISHDA YANGI PEDAGOGIK TEXNOLOGIYALAR - Xasanov, A.T.; Azimov, A.M. (SCIENCE and SOCIETY, 2022)
The article presents the results of a pedagogical experiment and their analysis in order to develop methodological recommendations aimed at further improving the professionally applied motor training of students, with an emphasis on professionally applied physical training.